First evidence on the occurrence of multi-mycotoxins and dietary risk exposure to AFB1 along the cassava value chain in Uganda - Oyesigye, Elias; Cervini, Carla; Oluwakayode, Abimbola; Mahuku, George; Medina, Angel (Springer, 2024)
This study investigated the occurrence and distribution of multiple mycotoxins (aflatoxin B1, B2, G1, G2, fumonisins B1, B2, ochratoxin A (OTA), deoxynivalenol (DON), zearalenone (ZEN), and citrinin (CIT)) in cassava products and as assessed the potential risk of aflatoxin B1 (AFB1) exposure among cassava consumers. A total of 192 samples of cassava products (96 flour and 96 chips, each with 48 samples from farmer and 48 from wholesaler) were analysed using LC/MS–MS. All positive samples irrespective of their origin (flour or chips) exhibited AFB1 levels exceeding the EU regulatory threshold of 5 µg/kg. The sum of fumonisins (FB1 + FB2), ZEN, and DON were significantly (P < 0.05) higher in cassava flour (14.3 µg/kg; 3.71 µg/kg; 25.1 µg/kg) compared to chips (6.54 µg/kg; 1.25 µg/kg; 0.25 µg/kg), respectively. Aflatoxins G2 was not detected in any of 192 samples. Cassava flour samples from farmers exhibited significantly (P < 0.05) higher mean concentrations of AFB1 (27.1 µg/kg), total aflatoxins (78.2 µg/kg), and ochratoxin A (79.6 µg/kg) in contrast to wholesalers, whose mean levels were notably lower at 8.91, 5.79 µg/kg, and 2.44 µg/kg, respectively, pointing the likely critical source of mycotoxin contamination. Cassava consumers in Northern Uganda are at a higher risk, with an estimated 2.06 cancer cases per 100,000 individuals per year compared to those in Eastern Uganda at 0.25. This study underscores the urgent need for interventions to manage aflatoxins in cassava flour, particularly at farm level in Northern Uganda. It accentuates a shift market to household-level sampling and the need for analytical methods targeting multiple mycotoxins.
Keywords: Mycotoxins; Cassava; Risk assessment; LC/MS-MS analysis; Uganda; 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; Cassava; LC/MS–MS analysis; Mycotoxins; Risk assessment; Uganda